A comparative study of optical nonlinearities of trans-A2B-corroles in solution and in aggregated state1. Issue 36 (23rd April 2015) - Garai, Antara; Kumar, Samir; Sinha, Woormileela; Purohit, Chandra Shekhar; Das, Ritwick; Kar, Sanjib
<x xml:space="preserve">Abstract</x> The NLO properties of a series of FB corroles are studied in the solution as well as in the aggregated state (in the form of thin films).